About samarium bromide - carbamide complexes - Yu. L. Alikberova; V. D. Albov; S. A. Bushmeleva; A. G. Fedorova; V. V. Kravchenko; S. N. Rukk (Тонкие химические технологии)
The synthesis and data of the study of new complexes of samarium bromides with carbamide, [Sm(Ur)4(H2O)4]Br3 (I) and [Sm(Ur)6(H2O)2]Br3 (II), by IR spectroscopy and X-ray diffraction analysis are presented. For these compounds, coordination with the metal occurs through the oxygen atoms of the water and carbamide molecules. The coordination polyhedra are distorted tetragonal antiprisms. The coordination of four carbamide molecules in I does not change their planar structures, but in II one carbamide ligand is distorted. The bromide ions are not coordinated and are situated in the external sphere. Many hydrogen bonds are observed in the structures of both complexes. Ключевые слова: комплексные соединения, самарий, бромид, карбамид, строение. Key words: complexes, structure, carbamide, samarium, bromide.